Animal cruelty in cat: case report - Monteiro, J. H.; Matsui, A.; Cuevas, S. E.; Honrado, S. A.; Vasconcelos, R. O.; Moreira, P. R. R. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Acts of cruelty against animals are considered a crime according to the Environmental Crimes Law, art. 32 (BRASIL, 1998). Abuse of cats is common and is practiced mainly by intentional exogenous intoxication and also by traumas (MARLET; MAIORKA, 2010; SIQUEIRA et al., 2012), in which blunt injuries are the most commonly observed (MUNRO; MUNRO, 2008; MCEWEN, 2012; CUEVAS et al., 2016). Forensic veterinary pathology is extremely important in cases of animal cruelty, not only to determine the animal’s cause of death, but also to help to differentiate between accidental and non-accidental lesions (MERCK et al., 2013). This is an important tool of forensic veterinary medicine, due to the legal potential of these types of cases. Therefore, this study aims to describe the lesions found in a cat killed in a cemetery, called “Cemitério da Saudade”, in Ribeirão Preto/SP, Brazil, with suspected abuse. A female, uncastrated, mixed breed cat and black hair was found dead in the “Cemitério da Saudade”, located in the city of Ribeirão Preto/SP, Brazil.